Intravenous thrombolysis prevents neurological deterioration in patients with acute pontine infarction - Chai, Zhenxiao; Chen, Weili; Ye, Yichan; Song, Mengwan; Lin, Lingling; Lin, Dongdong; Huang, Xuerong; Chi, Lifen; Huang, Ruyue (Frontiers in Neurology, 2025)
ObjectivesNeurological deterioration (ND) is common after acute isolated pontine infarction, and no evidence-based treatment is available to prevent this. We determined whether intravenous thrombolysis (IVT) with tissue plasminogen activator soon after pontine infarction prevents ND.MethodsWe retrospectively enrolled consecutive patients admitted to our hospital within 4.5 h after the onset of isolated pontine infarction identified using diffusion-weighted imaging. Patients were divided into the IVT and non-IVT groups. ND was defined as any ≥2-point increase in the National Institutes of Health Stroke Scale (NIHSS) score between the maximal and initial neurological deficits during hospitalization. Patients' clinical characteristics, laboratory findings, and outcomes were analyzed to determine the efficacy and safety of IVT.ResultsOf 211 study patients (median age, 67 years [interquartile range, 57–75 years]; 132 [62.6%] men), 74 received IVT; 137 patients did not receive IVT, but accepted other antithrombotic therapies, including antiplatelet or anticoagulant drugs. The NIHSS score on admission was higher in the IVT group than in the non-IVT group (7 vs. 4, P = 0.000), but that at discharge was similar in both groups (4 vs. 5, P = 0.975). ND occurred in 17 (23.0%) and 51 (37.2%) patients in the IVT and non-IVT groups, respectively (P = 0.044). Multiple logistic regression analysis identified IVT (odds ratio, 1.509; 95% confidence interval, 1.250–3.034) as an independent factor for preventing ND. The incidence of intracranial hemorrhagic transformation (P = 0.351) and major visceral organ hemorrhage (P = 0.122) was similar in both groups.ConclusionsIVT may prevent early ND after acute pontine infarction without increasing intracranial hemorrhagic transformation, possibly by decreasing the total thrombotic burden.